1. 4x - 8 + 2x + (-5x) + x^2 - 3 = 4x - 8 + 2x - 5x + x^2 - 3...now, we just combine like terms....lets group them...it will be easier ...x^2 + (4x + 2x - 5x ) - 8 - 3 = x^2 + x - 11
2. 2x + 5x = 8x
3. 2r + 4 + 3x - 2 = 3x + 2r + (4 - 2) = 3x + 2r + 2
4. 3x - 2y - x + 5y = (3x - x) + (5y - 2y) = 2x + 3y
5. 2y^2 - 8y^3 + 5y - 5y^2 + 4y^3 = (4y^3 - 8y^3) + (2y^2 - 5y^2) + 5y =
-4y^3 - 3y^2 + 5y
Converse Perpendicular Transversal Theorem.
If two lines are perpendicular to the same line, then the lines are parallel.
3^2 + 4^2 = 5^2
9 + 16 = 25
25 = 25
5^2 + 12^2 = 13^2
25 + 144 = 169
169 = 169
9^2 + 12^2 = 15^2
81 + 144 = 225
225 = 225
<span>a^2 + b^2 is = to c^2</span>
<h3>
Answer: 4</h3>
========================================================
Work Shown:
![\frac{2\sqrt{72}}{\sqrt{8}+\sqrt{2}}\\\\\frac{2\sqrt{36*2}}{\sqrt{4*2}+\sqrt{2}}\\\\\frac{2\sqrt{36}*\sqrt{2}}{\sqrt{4}*\sqrt{2}+\sqrt{2}}\\\\\frac{2*6*\sqrt{2}}{2*\sqrt{2}+\sqrt{2}}\\\\\frac{12\sqrt{2}}{2\sqrt{2}+\sqrt{2}}\\\\\frac{12\sqrt{2}}{3\sqrt{2}}\\\\\frac{12}{3}\\\\4](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Csqrt%7B72%7D%7D%7B%5Csqrt%7B8%7D%2B%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B2%5Csqrt%7B36%2A2%7D%7D%7B%5Csqrt%7B4%2A2%7D%2B%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B2%5Csqrt%7B36%7D%2A%5Csqrt%7B2%7D%7D%7B%5Csqrt%7B4%7D%2A%5Csqrt%7B2%7D%2B%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B2%2A6%2A%5Csqrt%7B2%7D%7D%7B2%2A%5Csqrt%7B2%7D%2B%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B12%5Csqrt%7B2%7D%7D%7B2%5Csqrt%7B2%7D%2B%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B12%5Csqrt%7B2%7D%7D%7B3%5Csqrt%7B2%7D%7D%5C%5C%5C%5C%5Cfrac%7B12%7D%7B3%7D%5C%5C%5C%5C4)
Note in step 2, I factored each number in the square root to pull out the largest perfect square factor. From there, I used the rule that
to break up the roots.